PSYCHOLOGICAL ANALYSIS OF LITERARY AND EDUCATIONAL VALUE IN THE NOVEL PSYCHOPATH TEST - Hari Kurniawan, Erwin (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2024)
This journal explores the relationship between literature and psychology, focusing on Jon Ronson's "The Psychopath Test." It examines the novel's structure, psychological insights, and its relevance as educational material in intensive reading classes. The text highlights the intertwining of psychology and literature, highlighting how psychological concepts are used to explore themes like identity, trauma, and personal growth. The passage also discusses the educational values of literature, including critical thinking, ethical awareness, understanding mental health, empathy, scepticism, interdisciplinary learning, and media literacy. The moral values learned from "The Psychopath Test" include empathy, ethical responsibility, compassion, justice, self-reflection, and the critical examination of power dynamics. The research methodology is a descriptive qualitative approach, utilizing a literary psychology approach.